Missing Information from the Estrogen Receptor Puzzle: Where Are They Localized in Bull Reproductive Tissues and Spermatozoa? - Antalikova, Jana; Secova, Petra; Horovska, Lubica; Krejcirova, Romana; Simonik, Ondrej; Jankovicova, Jana; Bartokova, Michaela; Tumova, Lucie; Manaskova-Postlerova, Pavla (Cells, 2020)
Estrogens are steroid hormones that affect a wide range of physiological functions. The effect of estrogens on male reproductive tissues and sperm cells through specific receptors is essential for sperm development, maturation, and function. Although estrogen receptors (ERs) have been studied in several mammalian species, including humans, they have not yet been described in bull spermatozoa and reproductive tissues. In this study, we analyzed the presence of all types of ERs (ESR1, ESR2, and GPER1) in bull testicular and epididymal tissues and epididymal and ejaculated spermatozoa, and we characterize them here for the first time. We observed different localizations of each type of ER in the sperm head by immunofluorescent microscopy. Additionally, using a selected polyclonal antibody, we found that each type of ER in bull sperm extracts had two isoforms with different molecular masses. The detailed detection of ERs is a prerequisite not only for understanding the effect of estrogen on all reproductive events but also for further studying the negative effect of environmental estrogens (endocrine disruptors) on processes that lead to fertilization.
Keywords: Receptors, G-Protein-Coupled; receptory pro estrogeny; Reproduction; bovine; spermie; rozmnožování; testis; reproduction; testes; zvířata; plasma membrane; Epididymis; Cattle; Testis; Male; Receptors, Estrogen; skot; epididymis; Spermatozoa; steroid hormones; Animals; mužské pohlaví; receptory spřažené s G-proteiny